Effects of infrastructure projects on government revenue: The case of expressway projects in the Northern Midland and Mountainous area of Viet Nam - Naoyuki Yoshino; Truong Thi Hoa (Asian Development Bank Institute (ADBI), 2020)
This paper examines the effects of infrastructure projects on economic performance by studying the changes in government revenue in the Northern Midland and Mountainous region of Viet Nam. More specifically, this paper investigates the effects of two expressway projects, namely (1) the Noi Bai-Lao Cai project and (2) the Ha Noi-Thai Nguyen project. In this study, we focus on the government revenue of the region, including personal income tax revenue, other government revenue from business activities, and total revenue, because they reflect the economic performance that the infrastructure investment creates. To investigate the impacts of infrastructure projects, we utilize the difference-in-difference (DID) method and compare the government revenue between the traversed regions and the non-traversed regions in two periods: (1) the construction phase and (2) the operation phase of the projects. The main estimated results show significant increases in the government revenue along the two expressways, highlighting an economic increase in the region after the completion of the expressway projects.
Keywords: H54; O11; O23; R11; 330; infrastructure; difference-in-difference analysis; tax revenues; Viet Nam